2011
DOI: 10.1158/1078-0432.ccr-11-1354
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Macrophages Promote Angiogenesis and Melanoma Growth via Adrenomedullin in a Paracrine and Autocrine Manner

Abstract: Purpose: Elevated numbers of tumor-associated macrophages (TAM) in the tumor microenvironment are often correlated with poor prognosis in melanoma. However, the mechanisms by which TAMs modulate melanoma growth are still poorly understood. This study was aimed at examining the function and mechanism of TAM-derived adrenomedullin (ADM) in angiogenesis and melanoma growth.Experimental Design: We established in vitro and in vivo models to investigate the relationship between TAMs and ADM in melanoma, the role and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
185
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(201 citation statements)
references
References 51 publications
7
185
2
4
Order By: Relevance
“…Research over the past decades revealed the remarkably diverse roles of macrophages in the growth and metastasis of solid tumors (8). In most cases, tumor cells secrete a variety of chemoattractants that attract macrophages and cause their accumulation in tumor tissues, wherein the macrophages become TAMs and play protumor roles (14,38,39). Compared with solid tumors, hematopoietic malignancies have unique features, and leukemia is characterized by impaired production of normal blast cells and the proliferation of leukemia blast cells principally in the BM (spleen in acute lymphoblastic leukemia) without solid mass (17).…”
Section: Discussionmentioning
confidence: 99%
“…Research over the past decades revealed the remarkably diverse roles of macrophages in the growth and metastasis of solid tumors (8). In most cases, tumor cells secrete a variety of chemoattractants that attract macrophages and cause their accumulation in tumor tissues, wherein the macrophages become TAMs and play protumor roles (14,38,39). Compared with solid tumors, hematopoietic malignancies have unique features, and leukemia is characterized by impaired production of normal blast cells and the proliferation of leukemia blast cells principally in the BM (spleen in acute lymphoblastic leukemia) without solid mass (17).…”
Section: Discussionmentioning
confidence: 99%
“…77 ADM/adrenomedullin , an antagonist of ADM receptors, suppresses tumor growth by skewing TAMs polarization to the M1 phenotype through downregulation of ADM in an autocrine-dependent manner. 75 These findings suggest that the identification of potential targets that polarize TAMs toward the M1 phenotype should be a promising anticancer strategy. By sensing the stimulation from the tumor microenvironment, macrophages are polarized to specific phenotypes through different signaling pathways, including the induction of autophagy.…”
Section: The Significance Of Macrophage Autophagy For Cancermentioning
confidence: 99%
“…16,21,75,76 TAMs are mainly polarized toward the M2 phenotype, that promotes tumor angiogenesis, growth, and metastasis. 16,21 However, it should be noted that some exceptions to this pattern exist.…”
Section: The Significance Of Macrophage Autophagy For Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it has been recently reported that in melanomas, TAMderived adrenomedullin is involved in angiogenesis and tumor growth. It was found that the adrenomedullin derived from TAMs interacts with its receptors on endothelial cells to promote tumor growth via a paracrine loop through the activation of the eNOS signaling pathway similar to the angiogenesis cytokine VEGF [90]. On the other hand, TAM-derived adrenomedullin can influence macrophages themselves in an autocrine manner, and, probably, may render immunosuppressive phenotype of tumor-associated DCs as well.…”
Section: Additional Tolerogenic Pathways In Regdcs: Neuropeptidesmentioning
confidence: 99%